COMPARISON OF HYDROCORTISONE 10 MG TABLETS: TABLET HARDNESS OPTIMISED FOR ADULT USE HAS NEGATIVE CONSEQUENCES FOR PAEDIATRIC USE. Issue 9 (17th August 2016) - Saimbi, Sarina; Madden, Valerie; Stirling, Heather; Yahyouche, Asma; Batchelor, Hannah
Abstract : Background: Children's medicines are not always readily available as an age appropriate product and manipulation of adult products is often required. Recently the commercial manufacturing process for 10 mg hydrocortisone tablets has changed and the compression force increased due to tablets fracturing on removal from the blister pack. However, this change led to parents of children requiring hydrocortisone reporting that the tablets were more difficult to manipulate. This study evaluated 10 mg hydrocortisone tablets for their suitability for manipulation in order to deliver an appropriate dose to children (2 mg dose). The physical properties of tablets with the old and new compression force were compared as well as the accuracy of obtaining the paediatric dose. Methods: The tablets compared were hydrocortisone Auden 10 mg tablets (Brand A, PL16876/002)-these are the newer, harder tablets- and hydrocortisone 10 mg tablets (Brand B, PL17507/0097). Tablet physical properties including friability (Copley FRV200) and tablet hardness (Copley TBF1000) were compared. The accuracy of split doses (halve and quarter tablets) were recorded on a Sartorius analytical balance. The accuracy of the 2 mg paediatric dosing was assessed by crushing the tablet, adding 10 mL of water and extracting 2 mL. The concentration was measured using UV analysis (Jenway Genova Plus) according to a calibration curve (wavelength=246 nm). Two devices were used to crush the tablets: a spoon onto a plate and a commercially available crushing device (Apothecary Ezy Crush Pill Crusher With Ergo Grip). Results: As anticipated Brand A tablets were harder (51.85 ±5.1 N) compared to Brand B (30.99±4.1 N). Brand A tablets passed the friability testing with <1% weight loss whereas Brand B failed as 5 tablets broke during testing. The accuracy of split doses using the score lines to halve and quarter the tablets showed that Brand A were generally better with smaller ranges for both halves (Range for A=41–55%; B=29–70%) and quarters (Range for A=17–35%; B=12–42%) compared to Brand B. The 2 mg dosing accuracy was better for Brand B tablets compared to A and crushing tablets using a commercial device improved the accuracy of dosing for both brands of tablets. When crushing using a spoon the mean dose obtained was 1.3 mg for Brand A and 1.7 mg for Brand B; the commercial crushing device gave values of 1.9 mg for Brand A and 2.1 mg for Brand B. Conclusion: Parents or carers who are required to manipulate 10 mg hydrocortisone tablets to administer a dose to children dispersed in water should be advised to crush the tablet into a fine powder where possible to improve the likelihood of administering an accurate dose. This is particularly important since the introduction of new hydrocortisone Auden tablets which are known to be harder tablets and therefore more force is required to crush these. Acknowledgements: Some of the experimental work within this project was conducted by Andrew Hackett and Kameron Paul-Thaper whilst at the University of Birmingham on work experience from Arden Sixth Form, Station Rd, Knowle, Solihull, West Midlands, B93 0PT.